Formulation and Physical Evaluation of a Kirinyuh (Chromolaena odorata L) Leaf Extract Patch as an Antipyretic in Male Wistar White Rats - Christin Aprilian Beama; Samanta Gabriel (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2026)
Long-term use of synthetic drugs can induce adverse side effects, prompting society to return to traditional medicine, such as kirinyuh leaves (Chromolaena odorata L.). Kirinyuh leaves contain flavonoid compounds that possess antipyretic potential by inhibiting the cyclooxygenase (COX) enzyme in prostaglandin synthesis. A transdermal patch formulation was selected to avoid absorption difficulties in the gastrointestinal tract and to improve patient compliance. This study aimed to formulate and evaluate the physical stability of transdermal patches containing kirinyuh leaf extract (at doses of 250 mg, 300 mg, and 350 mg) and to determine the most effective antipyretic dose in male Wistar rats (Rattus norvegicus) induced by 10% peptone. The extract was obtained through maceration using 96% ethanol, and the patches were prepared using the solvent casting method. Physical evaluation encompassed organoleptic testing, weight uniformity, pH, moisture content, thickness, and folding endurance. The antipyretic test was conducted on 25 male Wistar rats that had been acclimatized for 7 days. Baseline body temperatures were recorded prior to induction. The rats were then induced with 2 mL of 10% peptone via intraperitoneal injection, after which their temperatures were remeasured. The subjects were divided into 5 groups of 5 rats each: positive control (Bye-Bye Fever), negative control (blank patch), and three treatment groups (doses of 250 mg, 300 mg, and 350 mg). Rectal temperatures were monitored every 15 minutes for the first 2 hours and every 30 minutes during the final hour. The physical evaluation indicated that all patch formulas were stable and conformed to the physical quality standards for transdermal preparations. All three kirinyuh leaf extract patch formulas demonstrated antipyretic activity in reducing the rectal temperature of the rats. The 350 mg dose formulation provided the most effective reduction in body temperature 3,040C at the 180th minute, which was comparable to the positive control. The transdermal patch of kirinyuh leaf extract meets the physical stability requirements for transdermal preparations, and the 350 mg dose is the most effective antipyretic formulation.